Current Trends in Assistive Technology Education in Entry-Level Occupational Therapy Curricula. - Kanny, Elizabeth M.; Anson, Denis K. (American Journal of Occupational Therapy)
Objective. This replication study investigated what changes, if any, occurred in the education of entry-level occupational therapy students relative to assistive technology between 1989 and 1994-1995. Method. A questionnaire was mailed to all entry-level occupational therapy programs in the United States (N = 79). The response rate was 88.6% (n = 70). Results were compared with those of a similar survey that examined the same issues in 1989. Results. Assistive technology education had increased from 1989 to 1994-1995 in 11 identified areas. The highest increases were found in environmental access and robotics, sensory aids, augmentative communication, and prosthetics and orthotics. Only 10% of the respondent programs had less than 20 hours of assistive technology education compared with 50% in the earlier study. Thirty (43%) programs included one or more technology courses in the curriculum compared with 17 (29%) in 1989, and 62 (89%) programs included assistive technology content in lectures or units throughout the curriculum compared with 32 (54%) in 1989. Conclusion. Occupational therapy educators are placing more emphasis on assistive technology education than they did in 1989 and are learning the skills to teach this content. If this trend continues, we will see assistive technology content taught in all occupational therapy programs in the next millennium.